New Natural Gas Storage and Transportation Capabilities Utilizing Rapid Methane Hydrate Formation Techniques - Brown, T. D.; Taylor, C. E.; Bernardo, M. (National Energy Technology Laboratory (U.S.), 2010)
Natural gas (methane as the major component) is a vital fossil fuel for the United States and around the world. One of the problems with some of this natural gas is that it is in remote areas where there is little or no local use for the gas. Nearly 50 percent worldwide natural gas reserves of ~6,254.4 trillion ft3 (tcf) is considered as stranded gas, with 36 percent or ~86 tcf of the U.S natural gas reserves totaling ~239 tcf, as stranded gas [1] [2]. The worldwide total does not include the new estimates by U.S. Geological Survey of 1,669 tcf of natural gas north of the Arctic Circle, [3] and the U.S. ~200,000 tcf of natural gas or methane hydrates, most of which are stranded gas reserves. Domestically and globally there is a need for newer and more economic storage, transportation and processing capabilities to deliver the natural gas to markets. In order to bring this resource to market, one of several expensive methods must be used: 1. Construction and operation of a natural gas pipeline 2. Construction of a storage and compression facility to compress the natural gas (CNG) at 3,000 to 3,600 psi, increasing its energy density to a point where it is more economical to ship, or 3. Construction of a cryogenic liquefaction facility to produce LNG, (requiring cryogenic temperatures at <-161 °C) and construction of a cryogenic receiving port. Each of these options for the transport requires large capital investment along with elaborate safety systems. The Department of Energy's Office of Research and Development Laboratories at the National Energy Technology Laboratory (NETL) is investigating new and novel approaches for rapid and continuous formation and production of synthetic NGHs. These synthetic hydrates can store up to 164 times their volume in gas while being maintained at 1 atmosphere and between -10 to -20°C for several weeks. Owing to these properties, new process for the economic storage and transportation of these synthetic hydrates could be envisioned for stranded gas reserves. The recent ...